2013
DOI: 10.1007/978-1-4614-7651-1_8
|View full text |Cite
|
Sign up to set email alerts
|

Class II Fusion Proteins

Abstract: Enveloped viruses rely on fusion proteins in their envelope to fuse the viral membrane to the host-cell membrane. This key step in viral entry delivers the viral genome into the cytoplasm for replication. Although class II fusion proteins are genetically and structurally unrelated to class I fusion proteins, they use the same physical principles and topology as other fusion proteins to drive membrane fusion. Exposure of a fusion loop first allows it to insert into the host-cell membrane. Conserved hydrophobic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 99 publications
(158 reference statements)
2
40
0
Order By: Relevance
“…This similarity suggested that rGc had adopted its predicted post-fusion conformation, as recently evidenced for Andes virus Gc by sucrose sedimentation in an in vitro system [46]. Because attempts to crystallize the membrane inserted form of rGc failed, we introduced a mutation in the predicted fusion loop, which caused rosette formation upon concentration after detergent solubilization (in line with the model for insertion of trimeric post-fusion class II proteins into membranes, reviewed in [47, 48]). The fusion loop mutation was inspired by a recent report showing that the trimeric post-fusion form of the flavivirus class II fusion protein E could be crystallized in its post-fusion, trimeric form in the absence of detergent by replacing Trp 101 by histidine, as this residue is prominently exposed at the membrane facing-end of the post-fusion trimer [49].…”
Section: Resultssupporting
confidence: 53%
“…This similarity suggested that rGc had adopted its predicted post-fusion conformation, as recently evidenced for Andes virus Gc by sucrose sedimentation in an in vitro system [46]. Because attempts to crystallize the membrane inserted form of rGc failed, we introduced a mutation in the predicted fusion loop, which caused rosette formation upon concentration after detergent solubilization (in line with the model for insertion of trimeric post-fusion class II proteins into membranes, reviewed in [47, 48]). The fusion loop mutation was inspired by a recent report showing that the trimeric post-fusion form of the flavivirus class II fusion protein E could be crystallized in its post-fusion, trimeric form in the absence of detergent by replacing Trp 101 by histidine, as this residue is prominently exposed at the membrane facing-end of the post-fusion trimer [49].…”
Section: Resultssupporting
confidence: 53%
“…It has been shown that in class II membrane fusion proteins there is a hinge motion between domain I and II [reviewed in [19]], and mutations at that region affect the pH threshold for fusion. However it seems that in phlebovirus G C this region is more rigid [25].…”
Section: Resultsmentioning
confidence: 99%
“…In both routes, however, the virus is directed to an endosomal compartment where the glycoproteins respond to the reduced pH of the compartment with a sequence of conformational changes [17]. These conformational changes expose a hydrophobic motif, which is inserted into the endosomal membrane [18, 19]. The glycoprotein then folds back on itself, forcing the cell membrane (held by the fusion motif) and the viral membrane (held by a transmembrane anchor) to proximity, inducing the viral and endosomal membranes to fuse [2022].…”
Section: Introductionmentioning
confidence: 99%
“…for replication or extracellular milieu for another infection round), and is delivered in the form of trafficking vesicles (Humphries and Way, 2013;Modis, 2013;Rothman and Orci, 1992;Sun et al, 2013). Therefore, KDELR can be considered as intracellular receptors for DENV/RSP trafficking, whose function is akin to the role played by cell surface proteins in mediating viral entry.…”
Section: Discussionmentioning
confidence: 99%